2010
DOI: 10.1002/ejsp.739
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in social categories

Abstract: In this paper we review evidence from social, developmental, and evolutionary psychology to raise a common question: Are there priorities in how humans categorize their social world? Are some social groupings more prominent in childhood, and more resilient in adulthood than others? We review and compare evidence from each field, with a particular emphasis on exploring the relative robustness of gender, race, age, and language as social categories. We highlight the value of developmental approaches for characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 91 publications
5
124
0
Order By: Relevance
“…One interpretation is that the infants' responses were driven mainly by familiarity: Specifically, the infants preferred the woman whose language was familiar and, by association, the food or toy in her possession (e.g., Dunham, Baron, & Banaji, 2008;Kinzler, Shutts, & Correll, 2010).…”
Section: Do Infants Prefer Their Ingroup and Align Their Choices Withmentioning
confidence: 99%
“…One interpretation is that the infants' responses were driven mainly by familiarity: Specifically, the infants preferred the woman whose language was familiar and, by association, the food or toy in her possession (e.g., Dunham, Baron, & Banaji, 2008;Kinzler, Shutts, & Correll, 2010).…”
Section: Do Infants Prefer Their Ingroup and Align Their Choices Withmentioning
confidence: 99%
“…Infants also show preferences for faces of peers over those of adults (Bahrick, Netto, & Hernandez-Reif, 1998;Sanefuji, Ohgami, & Hashiya, 2006), indicating that age too is important as a basis for categorization. Recently, Kinzler, Shutts and Correll (2010) have found that a fourth form of categorization is apparent in infancy: native-language speakers versus foreign-language speakers. Although we have known for some time of newborns' preference for their mother tongue over other languages (Mehler et al, 1988;Nazzi, Bertoncini, & Mehler, 1998), recent work has revealed that pre-verbal infants even prefer to interact with and accept toys from speakers of their native language (Kinzler, Dupoux, & Spelke, 2007;Shutts, Kinzler, McKee, & Spelke, 2009).…”
Section: Social Categories Social Perception and Group Identitymentioning
confidence: 99%
“…Language is often a ubiquitous carrier of culture which allows people to become immersed in the group's norms, practices, and values (Fishman, 1999;Haarman, 1986;Kinzler, Shutts, & Correll, 2010). In some cultural groups, language is the only distinctive characteristic that defines one's ethnic group, and moving away from one's ethnic language is sometimes perceived as rejecting and distancing oneself from the ethnic group (Bailey, 2000;Fought, 2006;Yogeeswaran et al, 2011).…”
Section: Goals Of the Current Researchmentioning
confidence: 98%